Storytelling and Peer Education as Empowerment Communication among Muslim Creators in the TikTok Affiliate Ecosystem - Purwani, Diah Ajeng (Universitas Muhammadiyah Yogyakarta, 2026)
This study aims to explore the communication patterns of empowering content creators developing in Indonesia, focusing on the practice of TikTok Affiliate among Muslim content creators. The study employs a virtual ethnography method to analyze the forms of digital interactions, narrative constructions, and communication practices that empower Muslim content creators. The study results show that empowerment patterns emerge through story telling based personal narratives, peer education, and intensive community interactions. Creator activities are oriented to economic interests and interpreted as spaces to increase digital literacy, strengthen religious identity, and expand community-based economic networks. These findings confirm that TikTok can be a digital empowerment communication arena that balances economic motives and religious values. This article contributes to developing discourse on digital empowerment communication, participatory culture, and community-based innovation in the financial ecosystem of muslim creators in Indonesia. These findings underscore the significance of understanding the dynamics of social media as a novel space for identity formation, solidarity, and value-based economic empowerment.